Perencanaan Kurikulum Merdeka Di SMP Nurul Amal Palembang - Ibrahim Ibrahim; Dheista Galin A; Sherly Margareta; Nina Meilinda; Rendika Zulkipran (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
problem addressed here is the planning of the Free Curriculum learning which has not been implemented in the 9th-grade class of SMP Nurul Amal Palembang, Ilir Timur II Subdistrict, Palembang City. The purpose of this study is to determine how the Free Curriculum learning planning that has not been implemented in the 9th-grade class of SMP Nurul Amal Palembang. This research is a field study with a qualitative research approach. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve data collection, data presentation, and data verification stages. The informants in this study are the school principal, vice principal, teachers, and students. The results of this study show that SMP Nurul Amal Palembang has already implemented planning for Free Curriculum learning in the current era. The planning prepared by teachers includes the preparation of modules as a reference for conducting teaching and learning activities in the classroom. The school has also begun implementing the Free Curriculum and has conducted trials by applying it in classes VII and VIII, while class IX still uses the 2013 Curriculum.